Management indicators of the science, technology and innovation process in a Cuban university campus - Raquel de la Cruz Soriano; Onelia Guevara Reyes; Tamara Jiménez Padilla (Universidade Federal do Norte do Tocantins, 2020)
This work constitutes a contribution to the management of scientific research on a campus of a Cuban territorial university. The educational research methodology and methods were applied: document review, satisfaction survey with the science, technology and innovation process, brainstorming and the workshop. The achievement of results in scientific research was demonstrated through indicators of relevance, relevance and impact, expressed in: the execution of projects, scientific publications, national and international awards, recognitions to the institution in the forum of science and technique, and other municipal organizations.